Optimization of spacing and nitrogen dose for growth and flowering of statice (Limonium sinuatum) - JAIN, RITU; SINGH, M K; SWAROOP, KISHAN; REDDY, MAHALAKSHMI V; JANAKIRAM, T; KUMAR, PRABHAT; PINDER, ROHIT (The Indian Journal of Agricultural Sciences, 2018)
A field study was conducted at the Experimental Farm of Division of Floriculture and Landscaping, ICAR-IARI, New Delhi during 2014-15 and 2015-16 with the objective of determining the effect of spacing, nitrogen and their interaction on growth and flowering of statice (Limonium sinuatum Mill.). The experiment was laid out in factorial randomized block design with twelve treatments. The treatments consisted of three spacing viz. 30cm × 30cm (S1), 30cm × 45cm (S2) and 45cm × 45cm (S3) and four nitrogen doses viz. 10 g/m1 (N1), 20 g/m21 (N2), 30 g/m2 (N3) and was compared with control (N0). Data were collected for vegetative growth, flowering and biomass parameters of statice. Maximum plant height (83.60 cm) and spike length (23.89 cm) was recorded under S1N3, while the maximum plant spread (71.67 cm), number of cymes/spike (16.03), number of cut flowers/plant (19.66), cyme width (37.25 mm), spike diameter (5.67 mm) and flower longevity in the field (60.97 days) was observed under S3N2. However, the maximum number of primary branches/plant (30.78), number of secondary branches/plant (15.93), number of leaves (68.80), cyme length (65.50 mm), shoot fresh weight (851.83 g), root fresh weight (11.72 g), dry weight of shoot (194.23 g), dry weight of roots (5.28 g) and shoot root ratio (69.57) was recorded with S3N3.